Pregnant women's perception of gestational diabetes mellitus - Ferreira, Ednalva da Silva (2022)
Introduction: Diabetes that affects women during pregnancy is called gestational diabetes mellitus, which corresponds to carbohydrate intolerance in varying degrees of intensity, diagnosed for the first time during pregnancy and may or may not persist after delivery. Objective: to know the perception of pregnant women about gestational diabetes mellitus. Methods: this is a qualitative analysis study and the theoretical-methodological framework adopted was phenomenology. Data were collected through semi-structured interviews. Results: the participants were between 35 and 36 years old, were domestic and multiparous. It was observed that there were doubts about the disease itself and the pregnant women did not know the risks or complications that the disease could cause. However, most were concerned about what could happen and presented positive behaviors in relation to health, including in relation to diet, to avoid future complications. Final considerations: the perception of pregnant women in relation to the disease impacted on their behaviors and health habits and the need for information in view of the negative view of the disease.